MAIK’s Impact on The Indigenous Community in Kelantan State: Analysis in Terms of Welfare and Humanity - Muhammad Solihin bin Abd Razak; Nawi@Mohamad Nawi Bin Ismail (Rabbanica: Journal of Revealed Knowledge)
This article aims to highlight the welfare and humanitarian activities undertaken by the Council of Islamic Religion and Malay Customs of Kelantan (MAIK) in support of the indigenous community in Kelantan. MAIK is best known as an organisation that implements religious programs in indigenous villages. However, few people are aware of MAIK's assistance in ensuring the welfare of the indigenous community and humanitarian programs carried out in the interior. This demonstrates that MAIK is involved in welfare, humanitarian issues, and religious programs. This article was written to investigate MAIK's role in interest and humanity towards Kelantan's indigenous community. Therefore, writing this article is an effort to highlight the activities carried out by MAIK.